New developments in materials for infrastructure sustainability and the contemporary issues in geo-environmental engineering : Proceedings of the 5th GeoChina International Conference 2018 -- Civil Infrastructures Confronting Severe Weathers and Climate Changes: From Failure to Sustainability, held on July 23 to 25, 2018 in HangZhou, China /: Proceedings of the 5th GeoChina International Conference 2018 -- Civil Infrastructures Confronting Severe Weathers and Climate Changes: From Failure to Sustainability, held on July 23 to 25, 2018 in HangZhou, China. (2019) - Unknown
No abstract available